2012
DOI: 10.3892/mmr.2015.3468
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel resistance in MCF-7/PTX cells is reversed by paeonol through suppression of the SET/phosphatidylinositol 3-kinase/Akt pathway

Abstract: Breast cancer is one of the most prevalent types of malignant tumor. Paclitaxel is widely used in the treatment of breast cancer; however, the major problem contributing to the failure of chemotherapy in breast cancer is the development of drug resistance. Therefore, it is necessary to identify novel therapeutic targets and reversal agents for breast cancer. In the present study, the protein expression levels of SET, protein phosphatase 2A (PP2A) and phosphatidylinositol 3-kinase (PI3K)/Akt pathway were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Knockdown of transgelin 2 via small interfering RNA sensitized MCF-7/PTX cells to paclitaxel, and suppressed their migration/invasion abilities, suggesting that transgelin 2 might be a new biomarker for breast cancer (16). On the other hand, aberrant activation of the phosphatidylinositol 3 kinase/serine-threonine kinase (PI3K/Akt) pathway contributes to chemo-resistance, tumor metastasis and poor prognosis (17,18). Notably, we reported that the PI3K/Akt pathway was activated in MCF-7/PTX cells and the TAGLN2 -knockdown inhibited the PI3K/Akt pathway, suggesting that the PI3K/Akt pathway would be critical to breast cancer progression (19).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of transgelin 2 via small interfering RNA sensitized MCF-7/PTX cells to paclitaxel, and suppressed their migration/invasion abilities, suggesting that transgelin 2 might be a new biomarker for breast cancer (16). On the other hand, aberrant activation of the phosphatidylinositol 3 kinase/serine-threonine kinase (PI3K/Akt) pathway contributes to chemo-resistance, tumor metastasis and poor prognosis (17,18). Notably, we reported that the PI3K/Akt pathway was activated in MCF-7/PTX cells and the TAGLN2 -knockdown inhibited the PI3K/Akt pathway, suggesting that the PI3K/Akt pathway would be critical to breast cancer progression (19).…”
Section: Introductionmentioning
confidence: 99%
“…Using a full panel of HCC cell lines, we showed that the numbers of cancer cell colonies and tumor spheres were significantly reduced by SET knockdown; in contrast, overexpression of SET promoted the growth of HCC. More interestingly, our group and others have found that the activity of SET is associated with the development of resistance to standard anticancer drugs, namely chemotherapies or target therapies, in various malignant diseases (Agarwal et al, 2014;Cristobal et al, 2015;Hung et al, 2015Hung et al, , 2016Zhang et al, 2015). For example, ectopic expression of SET diminished the effects of paclitaxel against non-small cell lung cancer (Hung et al, 2015) and oxaliplatin against colon cancer (Cristobal et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…4). Because SET KD has been reported to decrease the protein levels of c-Myc and the phosphorylation levels of Akt in human breast cancer cells 16, 22 , we first examined the effects of SET KD on these signaling molecules in CIP-m cells (Fig. 4A,B).…”
Section: Resultsmentioning
confidence: 99%